Al-Quran: Antara Hijab dan Jilbab - Kustiana Arisanti (HUMANISTIKA : Jurnal Keislaman, 2015)
In tradition of previuos society, jilbab or veil habitually was weared by some one who did priglimage or someone who had predicate ustadzah and kiai’s wife, and in education area, jilbab was identically with someone who was graduated from pesantren. Then, It is hard to find someone wear jilbab at that time because jilbab is identic with the quality of someone’s faith. However, on nowdays, jilbab can not longer become a measurement of someone’s faith, but it is as part of fashion and what people wear. Next, there is a confusing term between jilbab and hijab, because some people see it as similar thing, but another see it as different. So, in this article is showed about the comparison, the difference and similarity between hijab and jilbab. This article tends to highlight the concept or hijab and jilbab either in its meaning, the explanation of al-qur’an about jilbab and hijab and the opinion of al-qur’an about hijab and jilbab.